Human factors engineering as a roadmap for organizational happiness: An opinions study of human resources sample working in technical college of administration- duhok - Odeesh, James (Humanities Journal of University of Zakho, 2022)
The current research comes within an effort to address and discuss the topic of current and future organizational happiness according to human factors engineering, the researcher deliberates put the human factors engineering and the balance of the existence of its requirements as a determinant and benefit from them in achieving organizational happiness and its dimensions at Technical College of Administration- Duhok, and the researcher conducted a quantitative study using descriptive statistics methods in the (SPSS V-25) program to test the correlation and influence between human factors engineering and its requirements (independent variable) and organizational happiness and its dimensions (dependent variable), and based on the data collected through the electronic questionnaire distributed to human resources working in Technical College of Administration- Duhok, which numbered (84) valid for analysis. The research reached many conclusions, the most important of which is the possibility of considering human factors engineering as a roadmap for achieving organizational happiness in Technical College of Administration- Duhok. Accordingly, many proposals have been made, the basis of which is that when achieving organizational happiness, policies and strategies must be developed and formulated, especially with regard to human factors engineering.